Analisis Nilai-Nilai Pendidikan Karakter Pada Lagu Wajib Nasional Dikelas Rendah - Vikriawati; Andi Nurrochmah; Iis Nurasiah (Jurnal Gentala Pendidikan Dasar, 2021)
The study aims to describe the value of character education in obligatory songs. The kind of research used on this research is a descriptive qualitative. The data drawn from this study are the lyrics to national obligatory songs. This research was conducted on April s/d in June. The data-reduction technique results in a way that results in data reduction, data presentation that is divided into two stages of data rating and decryption and interpretation of data and verification. Analyse of the character education values found in the national anthem have been found as many as 84 values which include 2 religious values, 3 value of tolerance, 8 value of discipline, 8 of democratic worth, 1 of democratic worth, 13 of patriotic passion, 34 of patriotism, 1 value of achievement, 4 of peace-loving values, 6 of environmental concern, 2 of social concern, and 1 of responsibility. The character education values found in compulsory national songs contribute to growing and shaping character education values in lower learners.